Improving City Development Performance: The Role of Regional Revenue, Financial Management, and Accountability - Rachman, Abdul Nasir; Fatma, Nur (Entrepreneurship Undergraduate Program at Amkop Business School, 2025)
This study aims to analyze the influence of Regional Original Revenue (PAD), regional financial management, and accountability, both partially and simultaneously, on development performance in Makassar City. This study will explain the causal relationship between variables through hypothesis testing. In this study, the analysis method used is a multiple regression analysis model using the SPSS program with 68 respondents. Based on the results of the study, Regional Original Revenue (PAD) has a significant influence on development performance, where the increase in PAD directly contributes to the improvement of development performance in Makassar City. In addition, better regional financial management has also proven to play an important role in supporting more optimal development performance. Accountability also has a significant influence, showing that the better the level of accountability, the better the development performance in Makassar City. Overall, PAD, regional financial management, and accountability together have a significant impact on development performance, where the synergy of these three factors will increase more effective development in Makassar City.Keywords: Regional Original Revenue, Financial Management, and Accountability, City Development Performance.